(3GdGWQGa GdQGUOI h GdeTGQcIs - (3Lhf(B, (3fhaSfLQs; (3cjfjK G cje(B, s ((3GdQjGV(B:s (3OGQ GdeQjN(B,s, 2010)
(3fXQI YGeI Mhd CUMGH GdeUdMI aj MhceI GdTQcI , MhGaR GdeOjQjf , ecGaMI GdZT GdeGdj HhGSWI GdeMGSHhf h GdeQGLYhf , eLdS GdGOGQI (B: (3JQTjO GdbQGQ GdGOGQj , Hfhc GdGSJKeGQ h eMddh GdGhQGb GdeGdjI (B: (3GYGOI GdgjcdI GdeGdjI , GdOGFfhf hhcGdGJ Jbjje GdGFJeGf (B: (3GdLOGQI GdGFJeGfjI , GdeSGgehf h GdYGFO Ydi GdCehGd GdeSJKeQI , GYGOI GdJfXje GdeDSSj (B: (3eONd GdOeL h GdVe , dLfI GdChQGb GdeGdjI h GdHhQUI (B: (3eYGdLI GdeeGQSGJ GdeGdjI h GdGOGQjI GdNGWFI , bhGYO LOjOI ddMhceI (B: (3bGfhf ChcSdj h SGQHfjR, GdeSDhdjI GdGLJeGYjI ddTQcI (B: (3ZjGH GdHYO GdGLJeGYj GdeDSSj (B.s
Keywords: (3GdChQGb GdeGdjIs; (3GdESJKeGQs; (3GdTQcGJs